2004
DOI: 10.1164/rccm.200401-033oc
|View full text |Cite
|
Sign up to set email alerts
|

Can Guideline-defined Asthma Control Be Achieved?

Abstract: For most patients, asthma is not controlled as defined by guidelines; whether this is achievable has not been prospectively studied. A 1-year, randomized, stratified, double-blind, parallel-group study of 3,421 patients with uncontrolled asthma compared fluticasone propionate and salmeterol/fluticasone in achieving two rigorous, composite, guideline-based measures of control: totally and well-controlled asthma. Treatment was stepped-up until total control was achieved (or maximum 500 microg corticosteroid twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
821
1
51

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,478 publications
(900 citation statements)
references
References 25 publications
27
821
1
51
Order By: Relevance
“…The results of numerous randomized and controlled clinical studies have demonstrated the efficacy of using ICS/LABA (an inhaled corticosteroid combined with a long-acting inhaled β 2 -agonist) in a single inhaler for the treatment of asthma of patients not controlled by low doses of inhaled steroids [21][22][23][24][25][26]. Moreover, it has been shown that the combination of these drugs considerably improved the management of asthma symptoms, including mild and severe exacerbations, as compared with the administration of ICS as monotherapy [27,28].…”
Section: Goals Of Asthma Managementmentioning
confidence: 99%
“…The results of numerous randomized and controlled clinical studies have demonstrated the efficacy of using ICS/LABA (an inhaled corticosteroid combined with a long-acting inhaled β 2 -agonist) in a single inhaler for the treatment of asthma of patients not controlled by low doses of inhaled steroids [21][22][23][24][25][26]. Moreover, it has been shown that the combination of these drugs considerably improved the management of asthma symptoms, including mild and severe exacerbations, as compared with the administration of ICS as monotherapy [27,28].…”
Section: Goals Of Asthma Managementmentioning
confidence: 99%
“…These SNPs cause coding changes of the amino acid (AA) product at each codon or amino acid position relative to the start codon. Denoted as AA 1 codon AA 2 (AA 1 and AA 2 referring to the amino acid products of the two differing alleles) these SNPs include Gly 16 Arg, Gln 27 Glu, Val 34 …”
Section: Adrβ2: the Genementioning
confidence: 99%
“…Two ADRβ2 polymorphisms, Gly 16 Arg and Gln 27 Glu, have both been shown to influence the downregulation of the β2-adrenergic receptor in Chinese hamster fibroblasts and human airway smooth muscle cells. 36,37 In Chinese hamster fibroblasts, substitution of the amino acid combination or haplotype Arg 16 27 ) results in resistance to isoproterenol-induced downregulaton of the receptor. 36 In human airway smooth muscle cells the findings were similar: receptors with the Gly 16 genotype underwent enhanced agonist-promoted downregulaton while the Gln 27 genotype showed attenuation of agonist-promoted desensitization with isoproterenol.…”
Section: Adrβ2 Pharmacogenetics At the Molecular Levelmentioning
confidence: 99%
See 2 more Smart Citations